Harnessing electronic healthcare data for wound care research: Standards for reporting observational registry data obtained directly from electronic health records. - Fife, Caroline E.; Eckert, Kristen A. (Wound Repair & Regeneration)
The United States Food and Drug Administration will consider the expansion of coverage indications for some drugs and devices based on real-world data. Real-world data accrual in patient registries has historically been via manual data entry from the medical chart at a time distant from patient care, which is fraught with systematic error. The efficient automated transmission of data directly from electronic health records is replacing this labor-intensive paradigm. However, real-world data collection is unfamiliar. The potential sources of bias arising from the source of data and data accrual, documentation, and aggregation have not been well defined. Furthermore, the technological aspects of data acquisition and transmission are less transparent. We explore opportunities for harnessing direct-from-electronic health record registry reporting and propose the ABCs of Registries (Analysis of Bias Criteria of Registries), which are an evaluation framework for publications to minimize potential bias of real-world data obtained directly from an electronic health record method. These standards are based on a point-of-care data documentation process using a common definitional framework and data dictionaries. By way of example, we describe a wound registry obtained directly from electronic health records. This qualified clinical data registry minimizes bias by ensuring complete and accurate point-of-care data capture, standardizes usual care linked to quality reporting, and prevents post-hoc vetting of outcomes. The resulting data are of high quality and integrity and can be used for comparative effectiveness research in wound care. In this way, the effort needed to succeed with the Quality Payment Program is leveraged to obtain the real-world data needed for comparative effectiveness research.